2014
DOI: 10.1021/jp501399k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Controlled Destabilization of an RNA Hairpin Structure by a Covalently Attached Azobenzene Switch

Abstract: As shown in recent experimental studies, photoswitches like azobenzene can act as efficient regulators of the folding and unfolding of DNA and RNA duplexes. Here we explore the details of the conformational changes induced by azobenzene attachment, focusing upon a small 14-mer RNA hairpin structure. The azobenzene chromophore is covalently bound to the stem region adjacent to a UUCG tetraloop which is known to represent a particularly stable structure. Since the characteristic time scale of conformational chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 59 publications
6
48
1
Order By: Relevance
“…The overall stability of the duplex is an interplay between hydrogen‐bonding and base‐stacking interactions. As observed in previous studies,42 a flipped out cis azobenzene disrupts the hydrogen‐bonding interactions between neighboring base pairs, but native‐like base stacking between azobenzene‐neighboring bases is observed. On the other hand, a trans azobenzene stabilizes the duplex due to increased stacking.…”
Section: Resultssupporting
confidence: 77%
“…The overall stability of the duplex is an interplay between hydrogen‐bonding and base‐stacking interactions. As observed in previous studies,42 a flipped out cis azobenzene disrupts the hydrogen‐bonding interactions between neighboring base pairs, but native‐like base stacking between azobenzene‐neighboring bases is observed. On the other hand, a trans azobenzene stabilizes the duplex due to increased stacking.…”
Section: Resultssupporting
confidence: 77%
“…41 The stacking interactions between any two bases can be mapped by monitoring either the center of mass distances or the buried surface area (BSA) between the bases and comparing them against mean values of these parameters obtained from reference simulations. 24,29 Here, we refer to the BSA, as in ref 29, but adopt a slightly modified approach to calculate the stacking stability. Let us consider the distribution of BSA between two bases calculated from a native RNA simulation where the bases remain visually stacked.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…22,28 Our recent modeling works in this field focused on the following two aspects: First, to develop a theoretical framework to capture the effect of the fast photoswitching dynamics on the slow conformational changes in DNA 29 and second, to analyze the destabilization of an RNA hairpin structure by covalently linked trans vs cis-azobenzenes. 24 In the second study, a detailed analysis of the effects of stacking and hydrogen bonding was given for the RNA hairpin structure. Here, melting temperatures were obtained for the azobenzene-substituted hairpin and it was found that T m cis <T m trans <T m native , in good qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 99%
“…711 Molecular dynamics (MD) simulations can be used to predict structure, 12,13 mechanism, 14 and dynamics 1518 which can then provide insight into function. RNA MD has been done both atomistically 1921 and with coarse-graining 22 and has a wide spectrum of applications.…”
Section: Introductionmentioning
confidence: 99%